(untitled) (Research, Society and Development, 2020)
Objective: Evaluate trigger accuracy for identifying adverse drug events (ADEs) in hospitalised elderly. Methods: Two hundred patients 60 years old from a medical clinic within a private hospital were followed-up. For ADE identification the adapted Global Trigger Tool tracker methodology was used. Causality was determined using the Naranjo Algorithm. Results: Of the 200 elderly patients included in the study, 106 were females (53%), the average age was 79 years, and the average length of hospital stay was approximately ± 10 days. Selected triggers were identified 1,457 times. The group of triggers with the best performance regarding its analysis accuracy was evolution triggers, with sensitivity of 69% and positive predictive value of 68%. In the individual performance analysis, the evolution tracker allergy, allergic reaction, pruritus achieved 100% performance for both sensitivity and positive predictive value. A total of 165 ADs were identified. Of these, 18% were phlebitis and 16% were hypoglycaemia. Drugs associated with ADE included insulin (15%) and Clarithromycin (9%). Conclusion: The triggering methodology has been effective for identifying ADEs. In addition, determination best trigger for constructing an ADE identification tool for hospitalised elderly was performed.